First, expand the terms in the parenthesis on the right side of the equation by multiplying each term within the parenthesis by the term outside the parenthesis:
#-2y - 22 = color(red)(2)(y + 3)#
#-2y - 22 = (color(red)(2) xx y) + (color(red)(2) xx 3)#
#-2y - 22 = 2y + 6#
Next, add #color(red)(2y)# and subtract #color(blue)(6)# from each side of the equation to isolate the #y# term while keeping the equation balanced:
#color(red)(2y) - 2y - 22 - color(blue)(6) = color(red)(2y) + 2y + 6 - color(blue)(6)#
#0 - 28 = (color(red)(2) + 2)y + 0#
#-28 = 4y#
Now, divide each side of the equation by #color(red)(4)# to solve for #y# while keeping the equation balanced:
#-28/color(red)(4) = (4y)/color(red)(4)#
#-7 = (color(red)(cancel(color(black)(4)))y)/cancel(color(red)(4))#
#-7 = y#
#y = -7#